A brief history of geology - O'Hara, Kieran D. (Cambridge Cambridge university press, 2018)
Approximately 200 years of the history of the development of the study of geology.
Includes brief biographies of the following: James Hutton (1726-1797), Abraham Werner (1749-1817), Georges Cuvier (1769-1832), William Smith (1769-1839), William Buckland (1784-1856), Adam Sedgwick (1785-1873), William Conybeare (1787-1857), Roderick Murchison (1792-1871), Charles Lyell (1797-1875), Louis Agassiz (1807-1873), Charles Darwin (1809-1882).
Keywords: Geology -- History; Geologists -- Biography